1997
DOI: 10.1183/09031936.97.10051015
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and postjunctional inhibitory effects of fenspiride on guinea-pig bronchi

Abstract: Fenspiride is a drug with potential benefits in the treatment of obstructive airways disease. It has antibronchoconstriction and anti-inflammatory properties. The aim of this study was to investigate the effect of this drug on the contractions induced in the guinea-pig isolated main bronchus and perfused lung by electrical field stimulation (EFS) or exogenously added agents.Bronchi were stimulated transmurally in the presence of indomethacin 10 -6 M and propranolol 10 -6 M, and isometric tension was measured. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
1
0
5
Order By: Relevance
“…It can be assumed that the bronchodilator effect of fenspiride in this case may be mediated not only via stimulation of afferent nerves, but also due to its direct relaxing effect upon smooth muscle cells. Girard et al (10) have found that fenspiride at low concentrations (10 −6 –10 −4  M) is able to reduce the release of neuropeptides including tachykinins from sensory presynaptic endings. At higher concentrations (>10 −4  M) fenspiride exerts its postsynaptic action directly on bronchial smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…It can be assumed that the bronchodilator effect of fenspiride in this case may be mediated not only via stimulation of afferent nerves, but also due to its direct relaxing effect upon smooth muscle cells. Girard et al (10) have found that fenspiride at low concentrations (10 −6 –10 −4  M) is able to reduce the release of neuropeptides including tachykinins from sensory presynaptic endings. At higher concentrations (>10 −4  M) fenspiride exerts its postsynaptic action directly on bronchial smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…В верхних дыха тельных путях, трахее и дистальных отделах Эреспал снижает гиперплазию бокаловидных клеток, секре тирующих муцин, уменьшает объем секреции и со держание в нем гексозы и фруктозы. С фармаколо гической точки зрения по механизму действия Эреспал, как и стероиды, оказывает ингибирующее действие на активность фосфолипазы А 2 (ФЛА 2 ), при этом если кортикостероиды ингибируют актив ность ФЛА 2 через индукцию синтеза специального белка ингибитора, то Эреспал блокирует транспорт ионов Са 2+ , необходимых для активации ФЛА2 [8][9][10]. Следовательно, по точке приложения противовоспа лительного действия и эффективности каскада арахидоновой кислоты Эреспал сопоставим с корти костероидами и, подобно им, прерывает формирова ние как простагландинов и тромбоксана, так и лей котриенов.…”
Section: резюмеunclassified
“…Следует отметить, что с появлением в арсенале врачей-педиатров препарата фенспирид появилась возможность патогенетической терапии ОРВИ, при которой кашель и другие проявления заболевания (отек, гиперемия и боль в горле, заложенность носа) купируются достоверно быстрее [17][18][19][20][21][22][23][24][25][26][27][28]. В настоящее время на российском рынке зарегистрированы несколько препаратов фенспирида, среди них -Сиресп (Medana Pharma, Польша).…”
unclassified
“…В Польше с 2011 г. Оказалось, что фенспирид обладает противовоспалительной активностью, за счет которой и достигается положительный клинический эффект. При этом по механизму действия фенспирид существенно отличается от таких классических противовоспалительных препаратов, как глюкокортикоиды и нестероидные противовоспалительные средства, что определяет отсутствие у фенспири-да осложнений, побочных и нежелательных эффектов, присущих классическим противовоспалительным лекарственным средствам [17][18][19][20][21].…”
unclassified
See 1 more Smart Citation